2021
DOI: 10.1159/000515299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spin in the Abstracts of Systematic Reviews and Meta-Analyses of Atopic Dermatitis Treatments and Interventions

Abstract: <b><i>Background:</i></b> Spin – the misrepresentation of a study’s results – has been identified in abstracts of studies focused on a variety of disorders from multiple fields of medicine. <b><i>Objectives:</i></b> This study’s primary objective was to evaluate the abstracts of systematic reviews and meta-analyses focused on the treatment of atopic dermatitis for the nine most severe forms of spin. <b><i>Methods:</i></b> We systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…Comparing our findings to that of other spin studies, abstracts of systematic reviews that focused on T2DM tend to have lower rates of spin 23–31 . For example, Ottwell et al found that 30% of systematic reviews focused on acne treatment contained some form of spin in the abstract 32 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Comparing our findings to that of other spin studies, abstracts of systematic reviews that focused on T2DM tend to have lower rates of spin 23–31 . For example, Ottwell et al found that 30% of systematic reviews focused on acne treatment contained some form of spin in the abstract 32 .…”
Section: Discussionsupporting
confidence: 64%
“…Comparing our findings to that of other spin studies, abstracts of systematic reviews that focused on T2DM tend to have lower rates of spin. [23][24][25][26][27][28][29][30][31] For example, Ottwell et al found that 30% of systematic reviews focused on acne treatment contained some form of spin in the abstract. 32 Similarly, Reddy et al found that 36% of systematic reviews on rotator cuff management contained spin in their abstract.…”
Section: Primary Findingsmentioning
confidence: 99%
“…Our team's previous investigations found spin in abstracts at rates ranging from 37% in oncology RCTs [18] to 70% in otolaryngology RCTs [37]. More recently, studies have shown that spin frequently occurs in abstracts of systematic reviews [38][39][40][41][42][43][44][45][46][47][48]. As previously mentioned, Ottwell et al [20] identified spin in 31% of the included abstracts of systematic reviews and meta-analyses on acne vulgaris therapies, a finding similar to ours.…”
Section: Xsl • Fosupporting
confidence: 86%
“…Both investigators are published authors on the topic of spin and well versed in identifying spin in systematic reviews. 18 , 23 The following characteristics were extracted for each study: (1) date of review search, (2) type of intervention/treatment (area of the body), (3) adherence to PRISMA guidelines, (4) funding source, (5) continent of origin of the first author, and (6) impact factor of the publishing journal…”
Section: Methodsmentioning
confidence: 99%
“…Spin has been shown to be prevalent in the systematic reviews of various medical treatments and interventions. 7 , 11 , 15 , 18 , 23 , 24 , 26 In a 2016 study, Yavchitz et al 30 created a classification system for the presence of spin in the abstracts of systematic reviews. These investigators determined the top 9 types of spin based on severity ( Table 1 ).…”
mentioning
confidence: 99%